1979
DOI: 10.1002/path.1711280206
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system alterations as sequelae of Venezuelan equine encephalitis virus infection in the rat

Abstract: Alterations of the Central Nervous System (CNS) in rats surviving acute infection with a virulent strain of Venezuelan Equine Encephalitis (VEE) virus were studied by light and electron microscopy. Cavitary necrosis of the cerebral cortex, macrophage activity and degenerative axonal changes were considered to be sequelae of the lesions induced during the acute phase of the infection. Mononuclear cell infiltrates of the neuropil, 3 mth after inoculation, were related to the immune response of the host. Focal le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The most intensively studied alphaviruses, including Venezuelan and eastern equine encephalitis viruses and SIN, develop a biphasic disease in infected amplification hosts that is characterized by high-titer viremia before the appearance of virus in the brain and encephalitis development (13,16,17). Viremia is also a prerequisite of a natural transmission cycle of alphaviruses that is required for infection of mosquito vectors.…”
Section: Discussionmentioning
confidence: 99%
“…The most intensively studied alphaviruses, including Venezuelan and eastern equine encephalitis viruses and SIN, develop a biphasic disease in infected amplification hosts that is characterized by high-titer viremia before the appearance of virus in the brain and encephalitis development (13,16,17). Viremia is also a prerequisite of a natural transmission cycle of alphaviruses that is required for infection of mosquito vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the murine model is characterized by biphasic disease, which starts with the productive infection of lymphoid tissue and ends in the destruction of the CNS by viral replication and a "toxic" neuroinflammatory response (12,13,15,16,39,42,43). By the time encephalitis has developed in an infected mouse, the infectious virus is usually absent from the peripheral organs and blood (12,13,15,16,39,42,43). However, virus replicates to high titers in the brain, and mice die 5 to 7 days after infection due to fatal encephalitis, as previously demonstrated with ZPC738 (2, 31).…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous infection of mice leads to biphasic disease with initial replication in lymphoid tissues, followed by viremia and penetration into and infection of the central nervous system (40), where the virus replicates until death of the infected animal occurs (12,13,16,39). The infection of the CNS results in an acute meningoencephalitis that leads to the death of large numbers of neuronal cells and 100% lethality in mice (18,27).…”
mentioning
confidence: 99%
“…During VEEV epizootics, equine mortality due to encephalitis can reach 83%; in humans, while the overall mortality rate is low (Ͻ1%), neurological disease including disorientation, ataxia, mental depression, and convulsions can be detected in up to 14% of infected individuals, especially children (25). Sequelae of VEE-related clinical encephalitis in humans and rats are also described (16,32). The predominant pathological findings in fatal human VEE cases reveal the following: (i) in the CNS, edema, congestion, hemorrhages, vasculitis, meningitis and encephalitis; (ii) in the lungs, interstitial pneumonia, alveolar hemorrhage, congestion, and edema; (iii) in lymphoid tissue, follicular necrosis and lymphocyte depletion; and (iv) in the liver, diffuse hepatocellular degeneration (10,11,26).…”
mentioning
confidence: 99%
“…VEEV infection of mice leads to a biphasic disease with initial replication in lymphoid tissues followed by viremia and penetration into the central nervous system (CNS), where the virus replicates until the death of the infected animal (16)(17)(18)24). The result of the CNS infection is acute meningoencephalitis that leads to massive death of neuronal cells (6).…”
mentioning
confidence: 99%